Characterisation and manipulation of docetaxel resistant prostate cancer cell lines - RANI, SWETA; O'DRISCOLL, LORRAINE (My University, 2011)
Background: There is no effective treatment strategy for advanced castration-resistant prostate cancer. Although Docetaxel (Taxotere?) represents the most active chemotherapeutic agent it only gives a modest survival advantage with most patients eventually progressing because of inherent or acquired drug resistance. The aims of this study were to further investigate the mechanisms of resistance to Docetaxel. Three Docetaxel resistant sub-lines were generated and confirmed to be resistant to the apoptotic and anti-proliferative effects of increasing concentrations of Docetaxel. Results: The resistant DU-145 R and 22RV1 R had expression of P-glycoprotein and its inhibition with Elacridar partially and totally reversed the resistant phenotype in the two cell lines respectively, which was not seen in the PC-3 resistant sublines. Resistance was also not mediated in the PC-3 cells by cellular senescence or autophagy but multiple changes in pro- and anti-apoptotic genes and proteins were demonstrated. Even though there were lower basal levels of NF-?B activity in the PC-3 D12 cells compared to the Parental PC-3, docetaxel induced higher NF-?B activity and I?B phosphorylation at 3 and 6 hours with only minor changes in the DU-145 cells. Inhibition of NF-?B with the BAY 11-7082 inhibitor reversed the resistance to Docetaxel. Conclusion: This study confirms that multiple mechanisms contribute to Docetaxel resistance and the central transcription factor NF-?B plays an immensely important role in determining docetaxel-resistance which may represent an appropriate therapeutic target.
PUBLISHED
doi: 10.1186/1476-4598-10-126 PMID: 21982118
Keywords: Oncology; Prostate Cancer; Cancer